Performance of CP Sugarcane Cultivars Grown in Different Locations in Florida - Robert A. Gilbert; James M. Shine, Jr.; Ronald W. Rice (EDIS)
SS-AGR-285,a 7-page illustrated fact sheet by Robert A. Gilbert,James M. Shine, Jr., and Ronald W. Rice,is part of the Sugarcane Handbook.It reports the results of a series of experiments that were designed to compare and contrast relative sugarcane cultivar performance at different locations throughout the Everglades Agricultural Area (EAA).Includes references.Published by the UF Department of Agronomy,October 2007.